1992
DOI: 10.1002/pro.5560011102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DNA binding and metal substitution on the dynamics of the GAL4 DNA‐binding domain as studied by amide proton exchange

Abstract: Backbone amide proton exchange rates in the DNA-binding domain of GAL4 have been determined using 'H-''N heteronuclear correlation NMR spectroscopy. Three forms of the protein were studied-the native Zn-containing protein, the Cd-substituted protein, and a Zn-GAL4/DNA complex. Exchange rates in the Zncontaining protein are significantly slower than in the Cd-substituted protein. This shows that Cd-substituted GAL4 is destabilized relative to the native Zn-containing protein. Upon DNA binding, global retardatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Cadmium ions are significantly larger than zinc ions, thus it would seem likely that the protein structure would alter in some manner to accommodate the larger cadmium ions. Indeed, 2D NMR (Gardner et al, 1991) and amide proton exchange results (Mau et al, 1992) are indicative of a more open structure for the Cd2 form of the protein. Despite these changes, the Cd for Zn substitution results in relatively modest changes in the affinity of the protein for its specific DNA sequence, 2-3-fold, compared to the = 103-fold preference for specific vs. nonspecific DNA under these gel conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium ions are significantly larger than zinc ions, thus it would seem likely that the protein structure would alter in some manner to accommodate the larger cadmium ions. Indeed, 2D NMR (Gardner et al, 1991) and amide proton exchange results (Mau et al, 1992) are indicative of a more open structure for the Cd2 form of the protein. Despite these changes, the Cd for Zn substitution results in relatively modest changes in the affinity of the protein for its specific DNA sequence, 2-3-fold, compared to the = 103-fold preference for specific vs. nonspecific DNA under these gel conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is exactly this point that calls into question the notion that allosteric pathways are precisely conserved across a family. The literature includes nearly countless examples demonstrating that protein structures and their dynamics are highly sensitive to small perturbations, regardless of whether the perturbation is mutation (53), ligand binding (54), or simply changing the type of metal ion bound to the protein (55). Related, several reports stress the diversity within dynamic signatures across protein families (56,57).…”
Section: A Critical View Of the Underlying Concept Of Conserved Allosmentioning
confidence: 99%
“…One should clearly keep in mind that the present analysis was performed on the biologically significant Zn complex and not on the Cd complex. Mau et al [28] have showed that some amide protons exchange 3–21× faster in Cd‐GAL4 than in Zn‐GAL4 and suggested that cadmium substitution is likely to cause a reduction of the global stability of the protein and of the recognition module. Rodgers et al [29] showed that the Zn for Cd substitution results in relatively modest changes (2–3‐fold decrease) in the affinity of a fragment of GAL4, comprising both the DNA‐binding domain and an additional subdomain (GAL4(149 * )), for its specific DNA sequence.…”
Section: Discussionmentioning
confidence: 99%